Maslov Index and Quasi-Symplectic Isomorphisms (Contemporary Mathematics, 2022)
Maslov index is defined as the number of the intersection of a loop of Lagrangian subspaces with a 1-codimensional cycle in the Lagrangian Grassmannian. It is well-known that linear symplectomorphisms preverse the Maslov index. We show how quasi-symplectic isomorphisms change Maslov index.
Keywords: Maslov index, linear symplectomorphism, Lagrangian Grassmannian